Regretting you - Hoover, Colleen (Montlake Romance, 2019)
"Morgan Grant and her sixteen-year-old daughter, Clara, would like nothing more than to be nothing alike. Morgan is determined to prevent her daughter from making the same mistakes she did. By getting pregnant and married way too young, Morgan put her own dreams on hold. Clara doesn't want to follow in her mother's footsteps. Her predictable mother doesn't have a spontaneous bone in her body. With warring personalities and conflicting goals, Morgan and Clara find it increasingly difficult to coexist. The only person who can bring peace to the household is Chris--Morgan's husband, Clara's father, and the family anchor. But that peace is shattered when Chris is involved in a tragic and questionable accident. The heartbreaking and long-lasting consequences will reach far beyond just Morgan and Clara. While struggling to rebuild everything that crashed around them, Morgan finds comfort in the last person she expects to, and Clara turns to the one boy she's been forbidden to see. With each passing day, new secrets, resentment, and misunderstandings make mother and daughter fall further apart. So far apart, it might be impossible for them to ever fall back together."--Amazon.com.